Suicide and Suicide Risk in Lesbian, Gay, Bisexual, and Transgender Populations: Review and Recommendations - Haas, Ann P. (Taylor & Francis, 2011)
Despite strong indications of elevated risk of suicidal behavior in lesbian, gay, bisexual, and transgender people, limited attention has been given to research, interventions or suicide prevention programs targeting these populations. This article is a culmination of a three-year effort by an expert panel to address the need for better understanding of suicidal behavior and suicide risk in sexual minority populations, and stimulate the development of needed prevention strategies, interventions and policy changes. This article summarizes existing research findings, and makes recommendations for addressing knowledge gaps and applying current knowledge to relevant areas of suicide prevention practice.